Job moves : 9 steps for making progress in your career - Bernstein, Ethan; Horn, Michael B.; Moesta, Robert, 1964- (Harper Business, an imprint of HarperCollins Publishers, 2024)
"Three innovators offer a framework for career development that helps anyone make real progress on their path when they switch jobs"--